Aberrant succination of proteins in fumarate hydratase-deficient mice and HLRCC patients is a robust biomarker of mutation status - Bardella, Chiara; El-Bahrawy, Mona; Frizzell, Norma; Adam, Julie; Ternette, Nicola; Hatipoglu, Emine; Howarth, Kimberley; O'Flaherty, Linda; Roberts, Ian; Turner, Gareth; Taylor, Jennifer; Giaslakiotis, Konstantinos; et al. (The Journal of pathology, 2011)
Germline mutations in the FH gene encoding the Krebs cycle enzyme fumarate hydratase predispose to hereditary leiomyomatosis and renal cell cancer (HLRCC) syndrome. FH‐deficient cells and tissues accumulate high levels of fumarate, which may act as an oncometabolite and contribute to tumourigenesis. A recently proposed role for fumarate in the covalent modification of cysteine residues to S‐(2‐succinyl) cysteine (2SC) (termed protein succination) prompted us to assess 2SC levels in our existing models of HLRCC. Herein, using a previously characterized antibody against 2SC, we show that genetic ablation of FH causes high levels of protein succination. We next hypothesized that immunohistochemistry for 2SC would serve as a metabolic biomarker for the in situ detection of FH‐deficient tissues. Robust detection of 2SC was observed in Fh1 (murine FH)‐deficient renal cysts and in a retrospective series of HLRCC tumours (n = 16) with established FH mutations. Importantly, 2SC was undetectable in normal tissues (n = 200) and tumour types not associated with HLRCC (n = 1342). In a prospective evaluation of cases referred for genetic testing for HLRCC, the presence of 2SC‐modified proteins (2SCP) correctly predicted genetic alterations in FH in every case. In two series of unselected type II papillary renal cancer (PRCC), prospectively analysed by 2SCP staining followed by genetic analysis, the biomarker accurately identified previously unsuspected FH mutations (2/33 and 1/36). The investigation of whether metabolites in other tumour types produce protein modification signature(s) that can be assayed using similar strategies will be of interest in future studies of cancer. Copyright © 2011 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.